Comparative transcriptomics of a generalist aphid, Myzus persicae and a specialist aphid, Lipaphis erysimi reveals molecular signatures associated with diversity of their feeding behaviour and other attributes - Sharma, Manvi; Oraon, Praveen Kumar; Srivastava, Rakesh; Chongtham, Rubina; Goel, Shailendra; Agarwal, Manu; Jagannath, Arun (Frontiers in Plant Science, 2024)
Aphids are phloem sap-sucking insects and are a serious destructive pest of several crop plants. Aphids are categorized as "generalists" or "specialists" depending on their host range. Myzus persicae (Sulz.) is a generalist aphid with a broad host range while Lipaphis erysimi (Kalt.), a specialist aphid, has a narrow host range. Aphid infestation involves several sequential stages including host recognition and selection, overcoming primary plant defence barriers, feeding on phloem sap and detoxification of host defence responses. Information on the molecular basis of variations between generalist and specialist aphids with reference to the above processes is limited. In the current study, we generated transcriptome data and analysed the differential expression of genes between M. persicae and L. erysimi in adult and nymph stages of development. Gene expression studies identified 7688 and 8194 differentially expressed unigenes at adult and nymph stages, respectively of M. persicae and L. erysimi. M. persicae showed significantly higher levels of expression in a greater number of unigenes (5112 in adults and 5880 in nymphs) in contrast to the specialist, L. erysimi in both developmental stages. In addition, M. persicae displayed a greater number (350 in adults and 331 in nymphs) of upregulated unigenes involved in important processes such as host recognition, plant cell wall degradation, detoxification, digestion and metabolism, which correlate with its dynamic and polyphagous nature in contrast to the specialist. Analysis of our transcriptome data for effector molecules, which facilitate the process of feeding and/or modulate host response against herbivory, led to the identification of several effectors which are being reported for the first time in our study. We observed a greater number of putative effectors in M. persicae (948 in adults and 283 in nymphs) than L. erysimi (797 in adults and 245 in nymphs). Based on our analysis, we conclude that the generalist aphid, M. persicae has a more diversified and stronger arsenal of genes that influence its polyphagous feeding behaviour and effective response to plant defence mechanisms against insect-herbivory. Our study provides a compendium of such candidate genes that would be most useful in studies on aphid biology, evolution and control.